Żołnierzy-Polaków wrażenia z podróży na front wojny rosyjsko-japońskiej - Jacek Legieć (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2017)
In the Russian-Japanese war in 1904–1905 about 50,000 Polish soldiers took part in the ranks of the Russian army. During the journey to the front of the Trans-Siberian Railway they had the opportunity to see Siberia for the first time. In letters to relatives and loved ones, they described their impressions of this trip. Unfortunately, very few of them have been preserved in the original, but fortunately many of them were reprinted by the Polish press during the war. Thanks to this, we can see what Polish soldiers remembered about this journey. The soldiers, mostly peasants, described the Siberian nature – mountains, forests, rivers, climate, Siberian cities and villages, the appearance and customs of their inhabitants. Separate fragments were also devoted to local food and prices of food products that increased significantly during the war. A lot of space is also occupied by descriptions of the Trans-Siberian Railway itself, especially bridges and tunnels that made a great impression on the soldiers. A separate place in the letters is occupied by fragments concerning the attitude of the soldiers themselves, religious life and meetings with the Poles living in Russia.